1997
DOI: 10.1097/00002060-199705000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Activity on Knee Joint Proprioception1

Abstract: Falls lead to significant morbidity and mortality in persons older than 65 years of age. Impaired proprioception may be a contributing factor to falls, and this may be influenced by the level of habitual physical activity. The primary purpose of this study was to investigate knee joint proprioception among young volunteers and active and sedentary elderly volunteers. Knee joint proprioception was measured through reproduction of static knee angles using a Penny and Giles electrogoniometer. The secondary purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(73 citation statements)
references
References 18 publications
5
65
1
Order By: Relevance
“…The limitation was not addressed as it is extremely difficult to accurately quantify one's lifelong history of physical activity. As a result, dividing participants based on the results of a physical activity questionnaire remains a common practice in motor control research (e.g., Adamo et al 2007;Adamo et al 2009;McGregor et al 2011;Petrella et al 1997;Pickard et al 2003;Wright et al 2011).…”
Section: Classification Of Physical Activity Level As a Study Limitationmentioning
confidence: 99%
“…The limitation was not addressed as it is extremely difficult to accurately quantify one's lifelong history of physical activity. As a result, dividing participants based on the results of a physical activity questionnaire remains a common practice in motor control research (e.g., Adamo et al 2007;Adamo et al 2009;McGregor et al 2011;Petrella et al 1997;Pickard et al 2003;Wright et al 2011).…”
Section: Classification Of Physical Activity Level As a Study Limitationmentioning
confidence: 99%
“…Indeed, several studies showed a relationship between aging and decline in several aspects of proprioceptive sensitivity, namely a decrease in joint position sense and an increase in movement detection threshold. The lower limb, knee joint position sense [6,27,30,37,49,51], and ankle joint position sense [41,55,76,82] are negatively affected by aging. Similarly, in the upper limb, a decline in elbow [56] and finger [19] joint position sense was observed.…”
Section: Evidence Of Proprioception Deterioration With Agingmentioning
confidence: 99%
“…Based on this, Petrella et al [51] designed a study to investigate knee joint proprioception among young volunteers and active and sedentary elderly volunteers. Knee joint proprioception was measured through reproduction of static knee angles using an electrogoniometer.…”
Section: Mechanisms Of Proprioception Deterioration With Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, abnormalities of the structures around joints due to injury or disease prevent proprioceptive functions from respond properly to movements, and may subsequently result in declines of posture control, protective reflex, joint motion, and balance reactions in response to postural disturbance 2,3) . Petrella et al 4) reported that joint reposition errors of elderly people, who were aged 65 or over, increased along with the aging, and that the increase was associated with the decline in the proprioceptive sense. Hurley et al 5) also reported that aging decreased joint position sense, accompanying muscle weakness of the lower limbs and decreases in standing stability.…”
Section: Introductionmentioning
confidence: 99%